Health Systems Barriers to the Implementation of Preventing Mother-to-Child Transmission of Human Immunodeficiency Virus Infection in Primary Health Care Facilities in Ghana - Beatrice Sarpomaa Osei; Peter Agyei-Baffour; Kofi Akohene Mensah; Peter Twum (Advances in Public Health)
Background. Ghana has implemented the prevention of mother-to-child transmission strategy (PMTCT) to control HIV infection transmission to babies. However, this has not yielded the desired results, as there are still many mother-to-child HIV infection cases being reported due to factors such as those related to health system barriers. This study was, therefore, conducted to identify health system barriers to the implementation of PMTCT in selected districts in the Ashanti Region of Ghana. Methods. A cross-sectional study was conducted among 118 health workers in 20 selected health facilities within the Asante-Akim Central and South Municipalities in the Ashanti Region, Ghana, to assess the health system barriers to the prevention of mother-to-child transmission of HIV/AIDS. Data was collected using a structured, self-administered questionnaire, which was later transferred to Kobo Collect software. The study participants were chosen using multistage sampling approaches. The data cleaning and analysis were done using STATA version 16.1. Multiple logistic regression models, chi-square analysis for normality testing, and descriptive analysis were all used. The results were displayed in tables, and a p-value of 0.05 was used to determine the significance level. The study was carried out from June to September 2022. Results. In all, 118 participants were involved in this study. Of this, 57.4% had a good level of knowledge of PMTCT, even though all of them were aware of PMTCT. We found being more than 40 years (Odds Ratio, OR = 2.08 95% CI: 1.05, 5.00) and being in service with Ghana Health Service for more than 15 years (OR = 2.36 95% CI: 0.51,10.84) to be significant predictors of knowledge on PMTCT among our participants. A greater proportion of our participants revealed inadequate staffing as the major challenge faced in the delivery of PMTCT in Ashanti Region. Increased education on PMTCT was the most suggested solution to improve the management of HIV infection among pregnant women and further enhance the success rates of PMTCT in Ashanti Region, Ghana. Conclusions. The majority of the health professionals had good knowledge about the prevention of mother-to-child transmission. However, the number of staff in the two districts was not adequate, which affected public education. It is therefore important to increase the number of staff to enhance educating the public and minimize the transmission rate in the districts and the country as well.